IMPLEMENTASI GMP BERDASAR PADA ISO/TS 22002-1 TERHADAP PRODUKSI IKAN TERI NASI (Stolepherus sp.) DI PT MARINAL INDOPRIMA - Sri Handayani; Lorine Tantalu; Rosalia May Nyonya (Agroindustrial Technology, University of Trunojoyo Madura, 2021)
ISO / TS 22002-1 is an excellent document to use as a requirement program in the application of a food safety management system for any food producer or processor. This guideline can be applied at PT. Marinal Indoprima, Pamekasan as a producer of dried anchovy (Stolepherus sp.) engaged in export. The purpose of this study was to analyze the application level of GMP base on ISO / TS 22002-1, quality control during the processing process and improvement efforts made by PT. Marinal Indoprima, Pamekasan. The data collection method is done by interview, observation and questionnaire. The fulfillment criteria are calculated based on the percentage of the score assigned to each Pre-Requisite Program (PRP) from number 4 to 17 (except for number 14 and 15). The results of the study inform that product quality control is carried out by means of inspection of raw materials, during processing and final products. Analysis of compliance with GMP (Good Manufacturing Practice) base on ISO / TS 22002-1: 2009 at PT. Marinal Indoprima Pamekasan, has very good qualifications in fulfilling PRP 7 (Waste Disposal), PRP 9 (Purchasing Management), PRP 16 (Warehousing), and PRP 17 (Product Information and Consumer Awareness), good qualifications in fulfilling PRP 4 (Construction and Building Layout), PRP 6 (Utility: Air, Water and Energy), PRP 8 (Equipment, Washing, Maintenance), and PRP 12 (Pest Control). Improvement efforts that need to be done by PT. Marinal Indoprima refers to the lack of qualifications in fulfilling PRP 5 (Layout of Workplace), and very poor qualifications in fulfilling PRP 10 (Prevention of Cross Contamination), PRP 11 (Cleaning and Sanitation) and PRP 13 (Sanitation and Personal Hygiene Facilities).